Biogenic amine content and microbiological quality of alpaca charqui - Salvá, Bettit K. (2018)
The content of biogenic amines and the counts of viable mesophilic aerobic bacteria, Staphylococcus aureus, Micrococcaceae, coliforms, molds and yeasts and lactic acid bacteria were analysed in 52 samples of alpaca charqui (30 samples of sliced charqui and 22 samples of charqui made with whole pieces with bone). Significant differences were observed in the microbial counts between sliced and whole-piece charqui, with higher microbiological counts in sliced charqui being found. Regarding the content of biogenic amines, a total average of 131.60 and 92.30 mg per kg of charqui were respectively found. The major biogenic amines found in sliced charqui were spermine (52.06 mg / kg), tryptamine + 2-phenylethylamine (28.75 mg / kg), tyramine (16.61 mg / kg) and putrescine (12.49 mg / kg). kg), whereas in the whole piece charqui the major biogenic amines were spermine (39.72 mg / kg), cadaverine (14.75 mg / kg), tyramine (14.71 mg / kg) and tryptamine + phenylethylamine (12, 18 mg / kg). Despite these differences, the presence of biogenic amines in both types of charqui were lower than the values considered as indicative of undesirable microbial activity. In addition, none of the charqui samples showed levels of the vasoactive biogenic amines (tyramine, histamine, tryptamine and 2-phenylethylamine), potentially harmful to the consumer's health, below the toxic levels of concern in food.